2017
DOI: 10.1039/c6ra28131a
|View full text |Cite
|
Sign up to set email alerts
|

Effective removal of chemical warfare agent simulants using water stable metal–organic frameworks: mechanistic study and structure–property correlation

Abstract: Water stable zirconium based MOFs are used for the efficient adsorptive removal of chemical warfare agent simulants from aqueous medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 68 publications
1
67
0
Order By: Relevance
“…The pure MOF is referred to as UiO66, while the composite is UiO66-C. The obtained dried powders were activated in high vacuum (10 −4 Torr) at 150 • C (using ASAP 2020, Micromeritics) and were kept in hermetically closed vials prior the use [63].…”
Section: Methodsmentioning
confidence: 99%
“…The pure MOF is referred to as UiO66, while the composite is UiO66-C. The obtained dried powders were activated in high vacuum (10 −4 Torr) at 150 • C (using ASAP 2020, Micromeritics) and were kept in hermetically closed vials prior the use [63].…”
Section: Methodsmentioning
confidence: 99%
“…Single-crystal X-ray diffraction showed that ReO 4 À ions bind in a unique chelating mode in both small pore and mesopore of NU-1000 in addition to two non-chelating modes in each pore, resulting in a promising adsorption efficiency. Asha et al 210 investigated NU-1000 toward the capture of two CWA simulants, 2-chloroethyl ethyl sulfide (2-CEES, the simulant of sulfur mustard gas), and dimethyl methyl phosphonate (DMMP, the simulant of sarin). NU-1000 performed efficient and reusable adsorption of the simulants from the aqueous medium.…”
Section: Adsorption and Separation Of Moleculesmentioning
confidence: 99%
“…Besides, the FT-IR spectra implied that the coordination of UiO-66-NH 2 after treatment with CEES was nearly similar to that of the original. However, there was a weak peak at around 1277 cm −1 (C−O−C vibration) and another two peaks at 1273 and 1065 cm −1 (CEES), 48 indicating the decomposition products of ether, bis [2-(ethylthio)ethyl], and less CEES remaining. Both these excellent characteristics and high catalytic detoxification further ensure engineering UiO-66- NH 2 @PAN fabrics for CWAs removal as a promising protection gear.…”
Section: Catalysis and Adsorption Of Ceesmentioning
confidence: 99%